Relationship Between Timing of Anterior Cruciate Ligament Reconstruction and Chondral Injuries: A Systematic Review and Meta-analysis. Issue 13 (November 2022) - Prodromidis, Apostolos D.; Drosatou, Chrysoula; Mourikis, Anastasios; Sutton, Paul M.; Charalambous, Charalambos P.
Background: After anterior cruciate ligament (ACL) injury, the optimal timing of ACL reconstruction and the influence of this timing on chondral damage remain unclear. Purpose: To assess the effect of timing of ACL reconstruction on the presence of chondral injuries via a systematic review and meta-analysis. Study Design: Systematic review and meta-analysis; Level of evidence, 4. Methods: Two reviewers independently performed systematic literature searches of 5 online databases using the Cochrane methodology for systematic reviews. Eligibility criteria were any comparative study of patients aged >16 years that assessed the relationship between timing of primary ACL reconstruction surgery and rates of chondral injuries. Meta-analysis was conducted using a random-effects model. Results: After screening, 14 studies (n = 3559 patients) out of 2363 titles met the inclusion criteria: 3 randomized controlled trials (n = 272), 3 prospective cohort studies (n = 398), and 8 retrospective cohort studies (n = 2889). In analysis of the studies, chondral injury rates were compared between ACL reconstructions performed before and after 3 time points: 3, 6, and 12 months after injury (eg, ≤3 vs >3 months). The rates of chondral injury increased with each time point. The increase was mostly due to low-grade injuries at 3 months (estimated odds ratio, 1.914; 95% CI, 1.242-2.949; P = .003), with the increase in high-grade injuries becoming predominant after 12 months (estimated odds ratio, 3.057; 95% CI, 1.460-6.40; P = .003). Conclusion: Our findings suggest that delaying ACL reconstruction surgery results in a higher rate of chondral injuries and the severity of these lesions worsens with time. These findings are comparable with those of our previously published study, which demonstrated a higher risk of meniscal tears associated with delayed ACL surgery. When ACL reconstruction is indicated, surgery ≤3 months after injury is associated with a lower risk of intra-articular damage. Registration: CRD42016032846 (PROSPERO).